# maths surd

(2+root(3))^6+[(2-root(3)]
without using calcultor

1. 👍 0
2. 👎 0
3. 👁 40
1. let
a=2+sqrt(3) b=2-sqrt(3)
but
a=((2+sqrt(3)^2)
b=[(2-sqrt(3)^2]
a^2=(2+sqrt(3))^2
=(2+sqrt(3)(2+sqrt(3)=7+4sqrt(3)
b^2=(2-sqrt(2)]^2
=(2-sqrt(3))(2-sqrt(3)
=7-4sqrt(3)
but
(a^3+b^3)=(a+b)(a^2-ab+b^2)
a+b=7+4sqrt(3)+7-4sqrt(3)
a+b=14
ab=(7-4sqr(3)(7+4sqrt(3)
ab=1
a^2=(7+4sqrt(3)(7+4sqrt(3)
=97+56sqrt(3)
b^2=(7-4sqrt(3)^2
b^2=(7-4sqrt(3)(7-4sqrt(3)=97-56sqrt(3)
a^3+b^3=(a+b)(a^2-ab+b^2)
=14(97+56sqrt(3)-1+96-56sqrt(3)
=14(97-1+97)
=14(193)=2702 yeah

1. 👍 0
2. 👎 0
posted by collins

## Similar Questions

1. ### Math simplifying mixed radicals

Please help me simplify these following mixed radicals:: and show me how you did it cause I need to learn : I don't know how to type a square root sign so I just wrote square root and the numbers infront of the square root are

asked by Miley on September 14, 2013
2. ### College Algebra

I need some help with a handful of questions. I need to see the steps on how to get to the final answers. I would also appreciate if you can explain how you got to those steps. Rationalize each expression by building perfect nth

asked by Krissy on January 21, 2013
3. ### College Algebra

I need some help with a handful of questions. I need to see the steps on how to get to the final answers. I would also appreciate if you can explain how you got to those steps. Rationalize each expression by building perfect nth

asked by Krissy on January 19, 2013
4. ### College Algebra help please

I need some help with a handful of questions. I need to see the steps on how to get to the final answers. I would also appreciate if you can explain how you got to those steps. Rationalize each expression by building perfect nth

asked by Krissy on January 20, 2013

Simplify A.1/root a +2 b.root 18/25 c.root a x cubed root a d.root x + 2 root y/root x-2 root y e.root5 x root72 /root 3

asked by Bettina on February 3, 2015
6. ### Math

Just need some help... Directions: Multiply or raise to the power as indicated... Then simplify the result. Assume all variables represent positive numbers. 1. 5(square root of 6) times two-thirds(square root of 15)= 3 one-third

asked by Anonymous on March 25, 2008
7. ### Algebra

Rationalize each expression by building perfect nth root factors for each denominator. Assume all variables represent positive quantities. I don’t understand how to compute these. Also I don’t have the square root sign so I

asked by Becca on January 18, 2013
8. ### Math

Rationalize the denominator. Assume that all expressions under radicals represent positive numbers. The square root of 3y^4 to the third root divided by the square root of 15x^4 to the third root. Here is what I have so far: I

asked by B.B. on May 21, 2010
9. ### Algebra

Can you explain how to find the solution of 3x^2-2x+5, using the quadratic formula? I got it down to (2 +/- sq. root of -56)/6. But my book then reduces that to (2 +/- 2 times the sq. root of 14i)/6. But I think in place of the 2

asked by Leyla on November 30, 2009
10. ### math

What does it mean to have the sqaure root of 5 with a 2 in front of it? How do you figure it out? 2 sqrt 5 is two times the square root of 5. It depends where the 2 is placed wrt the square root symbol. If it is on the same line

asked by Cookie on April 9, 2007

More Similar Questions